Interspecific Variation in the Physiological and Reproductive Parameters of Porcelain Crabs from the Southeastern Pacific Coast: Potential Adaptation in Contrasting Marine Environments - Guzman-Rivas, F (Elsevier Inc., 2018)
Porcelain crabs inhabit from upper intertidal to subtidal habitats. These environments are characterized by highly variable environmental conditions, which subject species found in these habitats to stress. In this study, we compared reproductive traits of mothers [i.e. fecundity, reproductive output (RO), dry weight, organic matter] and physiological parameters of their offspring (i.e. wet weight, water content, dry weight, organic matter, lactate content of embryos) of three species of porcelain crabs that inhabit the Southeastern Pacific: Petrolisthes laevigatus (upper intertidal); P. violaceus (low intertidal); Allopetrolisthes punctatus (subtidal). Overall, female P. laevigatus had lower fecundity (802 ± 115 vs. 4181 ± 1097 embryos) and amount of organic matter in their embryo masses (0.053 ± 0.006 vs. 0.27 ± 0.025 g) but higher RO values (1.34 ± 0.34 vs. 0.20 ± 0.07) than Allopetrolisthes punctatus. In addition, P. laevigatus embryos had higher organic matter content (81.09 ± 28.8 vs. 64.54 ± 6.1 μg), higher water content (188.6 ± 91.9 vs. 152.4 ± 30.8 μL) and higher lactate content (0.26 ± 0.04% vs. 0.07 ± 0.01% dry weight) than that found in A. punctatus embryos. Furthermore, females and embryos of P. violaceus showed low values and similar to those observed in P. laevigatus. As a potential strategy to increase survival of the offspring, P. laevigatus seems to invest a large portion of its energy in production of high quality embryos, despite costs to fecundity. This study reveals that porcelain crabs have physiological adaptations during their ontogeny that allow them to survive in fluctuating environments. © 2018 Elsevier Inc.